Social media engagement with transgender fertility content - Kajal Verma, M.D; Benette K. Sagun, B.S; Melody A. Rasouli, M.D., M.B.A; Cindy M. Duke, M.D., Ph.D (Elsevier, 2022)
Objective: To identify transgender fertility content with the highest online engagement on social media, determine its accuracy and quality, and see how this has changed over a 2-year period. Design: BuzzSumo, a content research tool, was used to identify the top 10 article links related to transgender fertility most interacted with on the social media platforms of Facebook, Twitter, Pinterest, and Reddit. We compared article links from June 2019 to June 2020 and from June 2020 to June 2021. The articles were categorized as accurate or misleading based on the references cited and current research. A qualitative analysis was performed using article references to scientific literature and journal impact factors. User engagement was compared with the accuracy of online information using descriptive and χ2 statistics. Setting: Not applicable. Patient(s): Not applicable. Intervention(s): Not applicable. Main Outcome Measure(s): Not applicable. Result(s): The top 10 article links for each time period were examined, with 7,077 total engagements. Fourteen articles referenced 14 unique scientific studies; no references were available for the remaining 6 articles. Alternative media was the primary source of popular article links, and accurate articles accounted for 74% of the total engagements. There was a significant association between the number of engagements with accurate articles and the time periods used for analysis (P < .0001). Conclusion(s): As the popularity of social media continues to rise, patients are more likely to turn to online platforms in search of information and advice regarding fertility. Transgender fertility is an emerging topic covered by scientific peer-reviewed journals, news organizations, and alternative media, and it is imperative for internet users to consider the accuracy of the information presented by social media platforms. Further, reproductive endocrinology and infertility physicians should use social media platforms to educate their patients on the topic of transgender fertility and prevent the spread of misinformation.